2013
DOI: 10.1074/jbc.m112.445429
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-92a Negatively Regulates Toll-like Receptor (TLR)-triggered Inflammatory Response in Macrophages by Targeting MKK4 Kinase

Abstract: Background: microRNAs (miRNAs) participate in innate immune responses. Results: miR-92a decreases rapidly in macrophages once stimulated with TLR ligands, and miR-92a controls inflammatory response by targeting MKK4/JNK/c-Jun pathway. Conclusion: TLR-mediated miR-92a reduction feedback enhances TLR-triggered inflammatory response. Significance: Our findings reveal a novel positive feedback loop in which TLR-reduced miR-92a expression functions to regulate the innate inflammatory responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(86 citation statements)
references
References 65 publications
3
80
1
2
Order By: Relevance
“…39,44 The presence of somatic hypermutations would suggest a memory B cell of origin; however, absence of CD27 and somatic hypermutations in a subgroup of WM patients 6,39,45,46 would favor, at least in the latter cases, a nongerminal center cellular origin. 48,49 ), and even several genes related to cellular development, growth and proliferation, as well as genes downstream of the interferon g regulator were found to be more active in CD22 low CD25 1 B-cells compared to the Waldenström clone. Interferon g-producing B cells have been recently described as a new subset that can promote innate responses against intracellular infection, via increased Bruton tyrosine kinase signaling and NF-kB activation, after CD40 ligation.…”
Section: Discussionmentioning
confidence: 99%
“…39,44 The presence of somatic hypermutations would suggest a memory B cell of origin; however, absence of CD27 and somatic hypermutations in a subgroup of WM patients 6,39,45,46 would favor, at least in the latter cases, a nongerminal center cellular origin. 48,49 ), and even several genes related to cellular development, growth and proliferation, as well as genes downstream of the interferon g regulator were found to be more active in CD22 low CD25 1 B-cells compared to the Waldenström clone. Interferon g-producing B cells have been recently described as a new subset that can promote innate responses against intracellular infection, via increased Bruton tyrosine kinase signaling and NF-kB activation, after CD40 ligation.…”
Section: Discussionmentioning
confidence: 99%
“…Ning et al [40] demonstrated a positive effect of miR-92a on the proliferation, differentiation, and survival of chondrogenic progenitor cells by targeting nog3, an inhibitor of the BMP signaling pathway. MiR-92a expression decreases rapidly in macrophages upon stimulation with Toll-like receptor ligands, and miR-92a controls the inflammatory response by targeting the MKK4/JNK/c-Jun pathway [41]. In our previous studies, we demonstrated that miR-92a-3p plays an important role in both cartilage development and degeneration via directly targeting HDAC2, and that siHDAC2 can also repress the expression of ADAMTS-4/5 in primary human chondrocytes [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…miR-146a is rapidly upregulated by LPS in human monocytic cells and regulates TLR4 signaling by targeting tumor necrosis factor (TNF) receptor-associated factor 6 (TRAF6) and interleukin-1 receptor-associated kinase (IRAK) [12] . miR-92a negatively regulates TLR-triggered inflammatory response in macrophages by targeting mitogen-activated protein kinase kinase 4 (MKK4) [13] . miR-21 is induced via the MyD88 pathway in macrophages www.nature.com/aps Sun Y et al Acta Pharmacologica Sinica npg triggered by LPS and controls inflammation by targeting proinflammatory tumor suppressor programmed cell death 4 (PDCD4) [14] .…”
Section: Introductionmentioning
confidence: 99%